Birth Restriction in The Perspective Of The Qur'an - Ulwan, Muhammad Naseh; Kholilurrohman; Zakaria Husin Lubis (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: Birth restrictions in the Al-Qur'an perspective are permanent birth restrictions prohibited in the Al-Qur'an because they are contrary to human nature, namely having offspring. However, in emergency situations, the Qur'an provides relief or allows birth restrictions to maintain maternal health. The discourse around birth control is currently increasingly urgent if it is related to the dense population of the world, especially the Indonesian population. Indonesia's population has now reached 270 million people with a population density of 140 people per square kilometer. If population density is not balanced with the State's ability to control it, it will give rise to problems such as poverty, health, education and crime. Therefore, in an emergency, birth control is one of the preventive options to reduce the rate of population growth. The problem that often arises when discussing the issue of limiting offspring is the quantity and quality of the population. This was triggered by the understanding that children are a gift from Allah and on the Day of Judgment the Messenger of Allah will be proud to see his many people. This understanding provides motivation for people to increase their offspring. However, on the one hand, Allah reminds us not to leave behind a weak generation, fearing that it will burden the family and the country.   Abstrak: Pembatasan kelahiran dalam perspektif Al-Qur'an adalah pembatasan kelahiran permanen yang dilarang dalam Al-Qur'an karena bertentangan dengan sifat manusia, yaitu memiliki keturunan. Namun, dalam situasi darurat, Al-Qur'an memberikan keringanan atau mengizinkan pembatasan kelahiran untuk menjaga kesehatan ibu. Wacana seputar pengendalian kelahiran saat ini semakin mendesak jika terkait dengan padatnya populasi dunia, khususnya penduduk Indonesia. Populasi Indonesia saat ini telah mencapai 270 juta jiwa dengan kepadatan penduduk 140 jiwa per kilometer persegi. Jika kepadatan penduduk tidak diimbangi dengan kemampuan Negara untuk mengendalikannya, itu akan menimbulkan masalah seperti kemiskinan, kesehatan, pendidikan dan kejahatan. Oleh karena itu, dalam keadaan darurat, KB menjadi salah satu pilihan preventif untuk mengurangi laju pertumbuhan penduduk. Permasalahan yang sering muncul ketika membahas masalah pembatasan keturunan adalah kuantitas dan kualitas populasi. Hal ini dipicu oleh pemahaman bahwa anak-anak adalah karunia dari Allah dan pada hari kiamat Rasulullah akan bangga melihat banyak umatnya. Pemahaman ini memberikan motivasi bagi orang untuk meningkatkan keturunannya. Namun, di satu sisi, Allah mengingatkan kita untuk tidak meninggalkan generasi yang lemah, takut akan membebani keluarga dan negara.